Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1161/atvbaha.109.190108
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Rheumatoid Arthritis Versus Diabetes

Abstract: Objective-The extent to which atherosclerosis is accelerated in chronic inflammatory diseases is not established. We compared preclinical atherosclerosis in rheumatoid arthritis with diabetes mellitus, a known coronary heart disease equivalent. Methods and Results-Endothelial function, arterial stiffness, carotid intima-media thickness, and analysis of atheromatous plaques were examined in 84 rheumatoid arthritis patients without cardiovascular disease versus healthy controls matched for age, sex, and traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
114
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 40 publications
(45 reference statements)
13
114
2
4
Order By: Relevance
“…Endothelial dysfunction was deteriorated to a similar extent in patients with systemic and nonsystemic JIA. Impaired FMD has been consistently observed in adult patients with CID, such as rheumatoid arthritis (11,13), as well as in children with Kawasaki disease (23), a systemic vasculitis that occurs mainly in younger ages. Recently, no difference in FMD between children/adolescents with systemic lupus erythematosus and healthy controls (24,25) was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction was deteriorated to a similar extent in patients with systemic and nonsystemic JIA. Impaired FMD has been consistently observed in adult patients with CID, such as rheumatoid arthritis (11,13), as well as in children with Kawasaki disease (23), a systemic vasculitis that occurs mainly in younger ages. Recently, no difference in FMD between children/adolescents with systemic lupus erythematosus and healthy controls (24,25) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…These findings probably reflect differences in methods used to assess aortic PWV in various studies. Increased PWV, a marker of adverse cardiovascular prognosis in various adult populations (5), has been demonstrated in adult CID patients (11,32) and children at high cardiovascular risk (7,33). LAEI and SAEI are relatively novel markers of arterial compliance that have been associated with cardiovascular risk factors (34,35) and CID in adults (36), but their value in cardiovascular prognosis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with RA had a similar carotid IMT and prevalence of carotid plaque as with age-and gender-matched patients with type 2 diabetes mellitus. The result thus suggested that both diseases contribute equally to the development of premature atherosclerosis [18]. A meta-analysis was performed involving 22 studies to estimate the overall mean carotid IMT difference between RA and control groups [19].…”
Section: Subclinical Atherosclerosis Carotid Intima-media Thicknessmentioning
confidence: 99%
“…1 Chronic inflammation is the most important reason for accelerated atherosclerosis development in RA. 2 Cytokines involved in the systemic circulation in RA have altered function in distant organs such as adipose tissue, liver, and skeletal muscle. Thus, they cause a series of atherogenic changes such as insulin resistance, dyslipidemia, oxidative stress, thrombotic effects, endothelial dysfunction, and injury.…”
mentioning
confidence: 99%